Inflammatory bowel disease: a narrative review of disease evolution in South Asia and India over the last decade - Sahana Shankar; Snehali Majumder; Suparna Mukherjee; Anirban Bhaduri; Rangarajan Kasturi; Subrata Ghosh; Marietta Iacucci; Uday N. Shivaji (Therapeutic Advances in Gastroenterology)
The rapid emergence of inflammatory bowel disease (IBD) in Asia in the last two decades is anticipated to pose significant challenges to the healthcare systems of developing countries including India. Several epidemiological factors in the Asia Pacific region have been explored as risk factors for the development of IBD. In this narrative review, we discuss the evolution of adult-onset and paediatric IBD in South Asia and India, in relation to the current global epidemiology, over the last decade. The focus lies on the changing epidemiological landscape of IBD in Asia which signals a paradigm shift in the disease trajectory of a chronic, relapsing, complex disease. We enumerate the disease burden of IBD in India and Asia, analyse the risk factors for its recent rise in incidence and briefly discuss the unique entity of very early-onset IBD. We also list the locoregional challenges in diagnosis and management along with suggestions to overcome them. We highlight the lacunae in data which warrants further research. The anticipated infrastructural challenges and disease evolution are likely to be similar in most newly industrialized countries across South Asia. A combined effort led by IBD experts in the region to understand the true disease burden is important. A strong collaborative network on research and formulation of preventive strategies relevant to the region will help reduce the burden in the future.